The influence of social media on adolescents' perceptions of HIV/AIDS - Purwanto, Edi; Charolina, Chika Helen Lola (Science Midwifery, 2025)
This study aims to analyze the dependent variable of perceptions about HIV/AIDS, influenced by the independent variables of age, gender, residence, education level, internet usage, social media usage, knowledge level, and stigma towards individuals in the community. The bivariate analysis showed that five variables significantly influenced social media usage, including place of residence with a p-value of 0.000*, education level with a p-value of 0.000*, internet use with a p-value of 0.000*, knowledge level with a p-value of 0.000*, and stigma with a p-value of 0.001*. The multivariate analysis revealed the variables influencing social media usage as follows: type of residence (Exp(B)=1.189; 95% CI=1.028-1.376; Sig=0.020*), education level (Exp(B)=4.304; 95% CI=3.819-4.852; Sig=0.000*), internet usage (Exp(B)=4.178; 95% CI=3.875-4.504; Sig=0.000*), knowledge level (Exp(B)=392.480; 95% CI=0.000-0; Sig=0.000*), and stigma (Exp(B)=0.023; 95% CI=0.894-0.978; Sig=0.000*). Adolescents in Indonesia are still vulnerable to misinformation and stigma from social media, influenced by various factors. However, the Chi-Square and logistic regression analyses showed that place of residence, education level, internet use, knowledge level, and stigma are the most significant factors. The hope is that researchers can further explore issues in adolescents' perceptions caused by social media use, beyond just misinformation and stigma. This aims to diversify the variables from the DHS data to reduce the risk of bias in comparison to previous research.